Apparent digestibility of a diet including sacha inchi (Plukenetia volubilis L) seed meal in growing creole pigs - Viamonte, María Isabel (2020)
The aim of this study was to determine the apparent faecal digestibility of a diet including sacha inchi (Plukenetia volubilis L) seed meal in growing creole pigs. Two male castrated pigs were used, body weight of 50 ± 2 kg, housed in metabolic cages, and under a 2x2 Latin square design. The pigs were fed diets with 0 (control) and 15% inclusion of sacha inchi seed meal, respectively. In the experimental diets and in the faeces it was determined: dry matter (DM), crude protein (CP), crude fibre (CF), fat, nitrogen-free extracts (NFE), gross energy (EB), calcium (CA) and phosphorus (P). The highest apparent digestibility coefficients of DM (82.38%) and P (32.32%) were obtained in the control diet (p<0.05). There were no significant differences for the digestibility of CP, CF, fat, NFE and Ca. In conclusion, the inclusion of 15% sacha inchi seed meal in the diet of growing creole pigs does not affect the apparent digestibility of CP, CF, fat, NFE and Ca, allowing a feed with high nutritional value.